User-centred Evaluations of Adaptive Systems - SHARP, MARY; WADE, VINCENT PATRICK; LAWLESS, SEAMUS; MULWA, CATHERINE (BCS, 2010)
Adaptive Hypermedia (AH) research is concerned with the dynamic composition and personalisation of hypermedia documents in order to provide more context sensitive retrieval and reuse of digital content. The evaluation of Adaptive Hypermedia Systems (AHS) is difficult due to the complexity of such systems [1]. Several Problems and pitfalls are encountered when evaluating these systems [2-6]. Very little research has been carried out to address this problem. This PhD work proposes a user-centred approach to the evaluation of the adaptive mechanism of AHS. The proposed approach will be validated using personalised systems developed by the Centre for Next Generation Localisation (CNGL). The framework developed by this research will help to standardise current approaches, offer hints regarding the identification of failures and misconceptions of the adaptive mechanism. It will be applicable to all adaptive systems with no limitations of domain or inference mechanism. A review of approaches, methodologies and techniques adopted by existing systems was conducted and the results analysed. An architectural design of the framework has been designed and currently implementation work is going on.
PUBLISHED
Keywords: Computer Science and Engineering; Adaptive Hypermedia (AH)